PENGEMBANGAN BAHAN AJAR BERBASIS KEARIFAN LOKAL DENGAN BERBANTUAN CANVA MENGGUNAKAN PENDEKATAN RME PADA MATERI BANGUN RUANG KELAS V DI SD SWASTA SABILINA - Sri Handayani; Landong, Ahmad; Dinda Fania Ardhini; Hunava, Nur; Syafrina, Riva (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics learning in elementary schools still faces various obstacles, particularly students' poor conceptual understanding of spatial geometry. Furthermore, the use of learning technology and the integration of local wisdom into the learning process have not been optimal. This study aims to develop local wisdom-based teaching materials using Canva, using the Realistic Mathematics Education (RME) approach, for fifth-grade students at SD Swasta Sabilina. This study employed the Research and Development (R&D) method with the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research instruments included validation sheets from material experts and media experts, teacher and student response questionnaires, and student learning outcome tests. Data were analyzed using descriptive quantitative methods. The product developed is a Canva-based digital teaching material that integrates local cultural elements into learning spatial geometry. The development of this teaching material is expected to produce a valid, practical, and effective product in improving students' understanding of mathematical concepts. Furthermore, the developed teaching material is expected to increase students' learning motivation and foster a love of local culture.